Introduction to the thematic issue on valuing research: theory, research, policy and practice of return on investment. (2nd January 2019) - Cohn, Joseph V.; Mutai, Jackie C.
Abstract: Increasingly, research enterprises in government, academia and industry are tasked with demonstrating the value of their undertakings. From the perspective of finite resources, like time, money and people, this is a reasonable request. Government researchers are duty-bound to demonstrate value to their nations' citizens, academic researchers are obliged to demonstrate value to their departments, and industry researchers are compelled to demonstrate value to shareholders and stakeholders. Yet, quantifying the "value" of research is a complex undertaking, with subjective advocacy often standing in place of objective analysis. Recent efforts demonstrate that it is possible to develop and apply methods for valuing research. This thematic issue provides a sampling of recent developments in the underlying theory and application of Return on Investment measurement and assessment.